Evaluation of Pre-Service Teachers' Views on the Reality Shock of the Teaching Practicum Course - Çakar, Nesligül; Özan, Mukadder Boydak (My University, 2025)
The purpose of this research is to evaluate the process of the teaching practicum course, where students in the elementary education department gain their initial professional experiences in primary schools affiliated with the Ministry of National Education, in the context of the expectation of reality shock. Additionally, the study aims to raise awareness among pre-service teachers regarding the reality shock they may encounter in the early years of their profession. The study group of this research consists of students enrolled in the Primary School Teaching program at İnönü University during the 2022-2023 academic year who have taken the Teaching Practicum I course. The participants include 6 females and 6 males, totaling 12 individuals who agreed to participate in the interviews. Research data were obtained using a semi-structured interview form consisting of 7 questions. The results of the research reveal that pre-service teachers experience role ambiguity in the teaching practicum course. They face challenges in selecting and implementing appropriate methods and techniques, preparing suitable materials for the course content, course planning, effective classroom management, effective communication, transitioning from theory to practice, handling class size and physical conditions, determining appropriate behavior towards special needs students, considering individual and developmental differences of students in conducting courses, and communicating with students with different mother tongues. Additionally, some pre-service teachers reported difficulties in their interactions with supervising teachers. Some pre-service teachers did not encounter issues in delivering theoretical and practical knowledge to students during the teaching practicum course. They resolved problems related to classroom management through the experiences gained during the internship and observations. Furthermore, they developed self-confidence and competence in class discipline and management over time, exhibited socio-cultural development, fostered positive attitudes towards the qualities of the profession, and acknowledged the contribution of subject knowledge courses, particularly acknowledging the preparation provided by professional knowledge courses for entering the profession and their utility in professional development.
Keywords: Pre-service teacher; elementary education; Reality shock; expectation of reality shock